Bismuth vacancy mediated single unit cell Bi2WO6 nanosheets for boosting photocatalytic oxygen evolution - Di, Jun (2020)
Surface defects are critically important for photocatalytic reactions. Compared with the widely studied oxygen vacancies, engineering metal vacancies into photocatalysts and study the effect of metal vacancies on the photocatalytic performance is seldom reported. Herein, we engineering bismuth vacancies into Bi2WO6 via a template-directed strategy to form single unit cell ultrathin nanosheets. Aberration-corrected scanning transmission electron microscopy reveals the formation of bismuth vacancies in the Bi2WO6 ultrathin nanosheets. Density functional theory calculations suggest that the presence of bismuth vacancies create a new defect level in forbidden band and increased density of states at the valence band maximum, resulting in increased charge carrier concentration and electronic conductivity. Moreover, the bismuth vacancy structure benefit for the surface adsorption and activation of water molecule, which favors the water oxidation reactions. As a result, the prepared bismuth vacancy-rich Bi2WO6 exhibit significantly increased visible light photocatalytic oxygen evolution activity than the corresponding bulk Bi2WO6, which is the more challenging half-reaction for fuel-forming due to the sluggish reaction kinetics. This work open the door for designing other metal vacancies engineered photocatalysts via ultrathin-control strategy and achieving highly efficient photocatalytic performances.